Alkaline thermal hydrolysis of sewage sludge to produce high-quality liquid fertilizer rich in nitrogen-containing plant-growth-promoting nutrients and biostimulants. (1st March 2022) - Tang, Yanfei; Xie, Hao; Sun, Jing; Li, Xiaoou; Zhang, Yue; Dai, Xiaohu
Highlights: ATH was superior in sludge reduction and organic n recovery due to using Ca(OH)2 . ATH significantly promoted the production of N-PGPN and N-PGPB in sludge liquor. ATH achieved highest N-PGPB, i.e. auxins and allelochemicals, production at 160 °C. ATH enriched more protein derived N-PGPB precursors before Maillard reaction. The ATH sludge liquor promoted crop growth without inducing soil contamination. Abstract: To produce liquid fertilizer containing nitrogen-containing plant-growth-promoting nutrients (N-PGPN) and plant-growth-promoting biostimulants (N-PGPB) from sewage sludge is attracting increasing interest recently, due to its superb fertilizing effect and the ease of application. Thus, this study aims to investigate the feasibility of producing high-quality liquid fertilizer with N-PGPN and N-PGPB recovery through alkaline thermal hydrolysis (ATH) using Ca(OH)2 . Results suggested that ATH treatment was superior in N solubilization (TSN/TN > 54%) and organic N maintenance in sludge liquor (> 80%) when compared to single thermal hydrolysis (TH). More surprisingly, ATH also promoted the production of N-PGPN and N-PGPB. As for N-PGPN, the maximum free amino acids (FAAs) accumulation in ATH liquor was 56.82 g/L at 120 °C while soluble protein (SPN) and soluble humic acid (SHA) reached 8.30–8.88 g/L and 1.88–2.05 g/L at 140–160 °C. The greatest N-PGPB produced by ATH treatment was achieved at 160 °C, with the detection of 1.156 mg/L phytohormones (indole-3-acetic acid and hydroxyphenyl acetic acids) and 4.95 mg/L allelochemicals (indolic derivatives and aromatic carboxylic acids). The 2D correlation FTIR maps analyses suggested, compared with TH, ATH could achieve protein hydrolysis before polysaccharides solubilization and denaturation with the temperature increased, thus avoiding Maillard reaction and benefiting N-PGPB production. Moreover, the laboratory investigation and field study indicated the usage of ATH liquor improved the growth of plants without inducing heavy metal contamination and soil salinization. Hence, ATH is a promising technology to produce high-quality liquid fertilizer rich with N-PGPN and N-PGPB from sewage sludge, especially suitable for such sludge with a low VS/TS ratio where biological treatment is inapplicable. Graphical abstract: Image, graphical abstract